2015
DOI: 10.1016/j.kjms.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

What is harmful for male fertility: Cell phone or the wireless internet?

Abstract: In this study, we aimed to assess the potential harmful effects of radiofrequency-electromagnetic radiation on sperm parameters. We requested semen for analyses from the male patients coming to our infertility division and also asked them to fill out an anonymous questionnaire. We queried their mobile phone and wireless Internet usage frequencies in order to determine their radiofrequency-electromagnetic radiation exposure. A total of 1082 patients filled the questionnaire but 51 of them were excluded from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 18 publications
0
28
0
2
Order By: Relevance
“…It has been recently reported that cellphones could cause infertility as well (36,37). Although the effects of cellphone EMR were investigated by many studies, some current results are controversial (5,38). Cellphone EMR waves induce oxidative stress and affect testicular structure and functions; (9) spermatogenesis is impacted (11,39) and it may lead to future infertility.…”
mentioning
confidence: 99%
“…It has been recently reported that cellphones could cause infertility as well (36,37). Although the effects of cellphone EMR were investigated by many studies, some current results are controversial (5,38). Cellphone EMR waves induce oxidative stress and affect testicular structure and functions; (9) spermatogenesis is impacted (11,39) and it may lead to future infertility.…”
mentioning
confidence: 99%
“…ICNIRP has declared 0.08W/kg as the tolerance limit for public health (ICNIRP, 2009). Infertility has also been demonstrated in different studies for electromagnetic radiation (Yildirim et al, 2015). From these perspectives of health complications, the main concern is that most of the people in this study were found to be unaware of the critical side effects of cell phones.…”
Section: Discussionmentioning
confidence: 60%
“…In regard to the effects of cellular phone RF‐EMW exposure on reproductive function, studies of spermatozoa have examined some long‐term effects of in vivo exposure in rats. One such study reported a significant reduction in the sperm motility rate [Mailankot et al, ], while other reports found no significant effects [Dasdag et al, ; Ribeiro et al, ; Imai et al, ; Yildirim et al, ]. In addition, we reported that cellular phone RF‐EMWs have no adverse effects on human spermatozoa [Nakatani‐Enomoto et al, ].…”
Section: Introductionmentioning
confidence: 56%